Exfoliated Graphitic Carbon Nitride Nanosheets as Efficient Catalysts for Hydrogen Evolution Under Visible Light - Yang, Shubin; Gong, Yongji; Zhang, Jinshui; Zhan, Liang; Ma, Lulu; Fang, Zheyu; Vajtai, Robert; Wang, Xinchen; Ajayan, Pulickel M. (Advanced materials (Weinheim), 2013)
Graphitic carbon nitride nanosheets are extracted, produced via simple liquid‐phase exfoliation of a layered bulk material, g‐C3N4. The resulting nanosheets, having ≈2 nm thickness and N/C atomic ratio of 1.31, show an optical bandgap of 2.65 eV. The carbon nitride nanosheets are demonstrated to exhibit excellent photocatalytic activity for hydrogen evolution under visible light.